The Effect of Entrepreneurial Characteristics and Self-Efficacy on Business Success in Bumi Waras District - Durroh Nihayah Hamhij; Risma Margaretha Sinaga; Novia Fitria Istiawati (International Journal of Educational and Life Sciences, 2024)
This research aims to determine the influence of entrepreneurial characteristics and self-efficacy on business success in Bumi Waras District. This research is quantitative research with research methods using descriptive verification. The population in this study was 124 food business actors. The number of samples in this study was 95 people, which were obtained using probability sampling techniques using simple random sampling. Data collection uses observation, interviews, questionnaires and documentation. Hypothesis testing was carried out using t and F tests processed with the SPSS program. The results of this research show that there is a simultaneous influence of entrepreneurial characteristics and self-efficacy on business success in Bumi Waras District with a coefficient of determination of 63.9% and the remaining 36.1% is influenced by other factors not examined in this research.